Respuesta :

Answer:

x = 1

Step-by-step explanation:

-3 + 4x + 3(4x + 8) = 4(7x + 3) - 3

first, solve the brackets by using the distributive property of multiplication:

3(4x + 8) = 12x + 24

4(7x + 3) = 28x + 12

rewrite equation:

-3 + 4x + 12x + 24 = 28x + 12 - 3

combine like terms:

16x + 21 = 28x + 9

subytact 21 on both sides:

16x + 21 - 21 = 28x + 9 - 21

16x = 28x - 12

subtract 28x on both sides:

16x - 28x = 28x - 28x - 12

-12x = -12

divide both sides by 12

[tex]\frac{-12x}{12} = \frac{12}{12}[/tex]

x = 1

to check, substitute 1 for x:

-3 + 4(1) + 3(4(1) + 8) = 4(7(1) + 3) - 3

-3 + 4 + 12 + 24 = 28 + 12 - 3

37 = 37

ACCESS MORE